Problems and Risks of the Modern World and the Ways of Their Solution - Borisovich Ivanov, Oleg (International Journal of Engineering and Technology, 2018)
The article deals with global problems and threats that greatly impact society in our time. The political and economic situation in the modern world is characterized by extreme tension and instability. Crisis phenomena cover all spheres of human life. In this situation, a reliable assessment of global risks is extremely important. Experts of the World Economic Forum conduct systematic work on the analysis and synthesis of the most dangerous risks for the world community. The theme of the current forum, â€œCreating a common future in a split worldâ€, points to the main world problem â€“ disunity in todayâ€™s global society. The main global risks of 2018 and the following period, according to experts, are the problems of climate and the environment; threats of a new technological wave and an increasing stratification of the level of incomes of the population. The destabilizing factor in the world was also the crisis of globalization. Prime Minister of India N.Modi called the crisis of globalization one of the main problems of mankind, along with climate change and terrorism. He stressed that protectionism becomes a global threat hampering world development.The paper examines the impact of risk groups and certain global threats on society, analyzes views on the problem of various expert centers, and formulates conclusions.Â Â